2013
DOI: 10.1177/0961203313499958
|View full text |Cite
|
Sign up to set email alerts
|

Physician-patient interactions and outcomes in systemic lupus erythematosus (SLE): a conceptual model

Abstract: The study findings informed a conceptual model of SLE patient-centered care that may be used to create more targeted education programs in the management of SLE, with the goal to improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…It is very important that a patient understands the substance of their disease, potential therapies, and factors that may affect the disease course. Cooperation with a doctor and patient awareness are of the key importance in such situations [20]. The awareness among our patients was good.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It is very important that a patient understands the substance of their disease, potential therapies, and factors that may affect the disease course. Cooperation with a doctor and patient awareness are of the key importance in such situations [20]. The awareness among our patients was good.…”
Section: Discussionmentioning
confidence: 55%
“…As much as 65.7% of patients stated that they possessed sufficient information on the disease, and 64% of patients stated that they were also aware of the therapy options. Sufficient patient awareness is one of the prerequisites for a successful therapy of SLE [20]. The most frequent sources of information for our patients were their attending doctor and the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…While we noted correspondences between various disease parameters and treatment satisfaction, cause and effect could not be established, although a cross-sectional survey of adults with SLE in the US has shown that steroid use was significantly associated with reduced patient satisfaction. 22 Despite its limitations, the current study is more likely to represent “real-world” findings than a controlled clinical trial. Additionally, this study provides the patient’s perspective, which is usually missing in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…m = 11.21; 95% CI 5.73–16.69; p < 0.001). Higher education level predicted and being white predicted more active participation Beusterien et al [ 24 ] To assess relationships between physician–patient relationship and patient outcomes including health status and regimen satisfaction in SLE USA Cross-sectional survey 302 SLE Patients’ perceptions of treatment regimen and satisfaction, physician–patient interactions including involvement in treatment decisions, physician bedside manner, satisfaction with physician, SLE control and severity, current health and hope about future health Positive physician–patient interactions led to higher satisfaction with treatment regimen and feeling well-controlled and more favourable perceptions of current health and being more hopeful about future health ( t = 6.10; t = 4.07) Ward et al [ 25 ] To examine associations between active patient–physician communication and measures of morbidity in patients with SLE USA Cross-sectional questionnaire study 79 SLE Patient communication behaviours coded as question asking, assertive responses, expressions of concern. Outcome measures assessed: depression (CES-D), SLE activity and morbidity SLAM, SLEDAI, SLICC/ACR Damage Index, Health Assessment Questionnaire (HAQ) Patients who participated more actively in their visits with physicians had less cumulative organ damage due to SLE.…”
Section: Methodsmentioning
confidence: 99%